Pendampingan Program Technocreator dan Perancangan Kurikulum Ekstrakurikuler Robotik untuk SMAK 1 BPK Penabur Bandung: Technocreator Program Support and Robotic Extracuricular Curriculum Design for SMAK 1 BPK Penabur Bandung - Halim, Levin; Naa, Christian Fredy; Arthaya, Bagus; Saputro, Nico; Sadiyoko, Ali (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community service establishes a collaborative effort between Parahyangan Catholic University and SMAK 1 BPK PENABUR Bandung to enhance the TechnoCreator program through community involvement. The program aims to enhance students' understanding of electronics by incorporating advanced technologies like the Internet of Things (IoT) and machine learning. It also introduces the concepts of Industry 4.0 and technopreneurship. The research entailed conducting a series of focused group talks, often known as focus groups, to ascertain the material and learning requirements. Additionally, an extracurricular curriculum for robotics was developed. The outcomes are the creation of novel educational programs, maintenance of guest lectures, strategic planning for the construction of an ESP32-based Internet of Things kit, the design of a prototype industrial automation system, and the implementation of a supplementary robotics program aimed at enhancing students' preparedness for advanced studies in electrical engineering. The activity also seeks to facilitate the transfer of students from secondary education to college. The result implies that this project effectively enhances student learning experiences and can be used as a blueprint for comparable technology education programs in the future.